Efficacy of psychomotor therapy for children and adolescents with anxiety disorders—a systematic literature review - Vriend, Evelien; Moeijes, Janet; Scheffers, Mia (Frontiers in Child and Adolescent Psychiatry, 2024)
Specific Phobia (SP), Generalized Anxiety Disorders (GAD), and Social Anxiety Disorder (SAD) are the most prevalent anxiety disorders in children and adolescents. Although anxiety has a major influence on the body, evidence-based treatments mainly focus on cognitive and behavioral aspects of anxiety. Body-and movement-oriented interventions, such as psychomotor therapy (PMT), address the physical aspects. Bodily experience and interoceptive awareness are used to change behavior, cognition, and emotions. This review aimeds to provide an overview of the efficacy of PMT for children and adolescents aged 0-18 years with SP, GAD, or SAD. [Method] Data waswere collected in PsycINFO, Medline, Embase, ERIC, and Web of Science, from January 2020 until April 2022. Two independent researchers (EV and JM) selected the articles and performed a critical appraisal.[Results] From 1438 articles found, only one article met the inclusion criteria.[Conclusion] No consensus-based statement about the efficacy of PMT in children and adolescents with SP, GAD, or SAD can be made due to the gap in the literature. Future research is needed to evaluate the efficacy. The first step may be to design treatment protocols. Subsequently, these protocols may be evaluated concerning efficacy.